2009
DOI: 10.1016/j.jpeds.2009.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Brain Volumes and Cognitive and Perceptual Correlates in 15-Year-Old Adolescents with Low Birth Weight

Abstract: Objective The aim of this study was to examine whether preterm very low birth weight (VLBW) or term born small for gestational age (SGA) adolescents have a reduced regional brain volume. Furthermore, we examined what perinatal factors are related to reduced brain volume in VLBW adolescents, and which regional brain volumes are associated with cognitive and perceptual functioning, and if these differ between the groups. Study design Fifty adolescent preterm VLBW (≤1500g) births and 49 term SGA births (birth wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
92
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(105 citation statements)
references
References 31 publications
13
92
0
Order By: Relevance
“…14 Our study found that global WM volume and CC area were also good predictors of IQ for the 7 SGA children in this sample. Importantly, our data raise the possibility that the relationship between WM and IQ is different in termborn and preterm brains, because correlations were undetectable in term-born controls, despite a comparable IQ range.…”
Section: Discussionsupporting
confidence: 54%
“…14 Our study found that global WM volume and CC area were also good predictors of IQ for the 7 SGA children in this sample. Importantly, our data raise the possibility that the relationship between WM and IQ is different in termborn and preterm brains, because correlations were undetectable in term-born controls, despite a comparable IQ range.…”
Section: Discussionsupporting
confidence: 54%
“…In some developing countries 16-50% of term infants are SGA, and the poor home environment in many of the countries adds to the risk of suboptimal development in these children (2). Various studies in humans have shown that being born underweight is a risk factor for cognitive deficits (3)(4)(5)(6)(7)(8), learning problems (4,9), spatial orientation difficulties (10), attention problems (9), depression (11), reduced brain volume (8), and reduced academic achievement and professional attainment (12) later in life.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that the hippocampus is a significant predictor of cognitive functioning in human adolescents who were born SGA (8). The cognitive hole-board task is a hippocampusdependent task (22).…”
Section: Methodsmentioning
confidence: 99%
“…The consequences of diffuse white matter degradation also involve cortical, basal ganglia, and cerebellar abnormalities (Counsell et al 2003;Kesler et al 2006). Notably, white matter injury appears to be the most common brain abnormality in preterm infants, and a major predictor of smaller volumes along with gestational age (Martinussen et al 2009). …”
Section: In-utero Effectsmentioning
confidence: 99%